Organization-based self-development prescriptive model for the promotion of professional development of Iranian clinical nurses - Flora Rahimaghaee; Nahid Dehghan Nayeri; Eesa Mohammadi; Shahram Salavati (Wolters Kluwer Medknow Publications, 2015)
Background: Professional development is reiterated in the new definition of modern organizations as a serious undertaking of organizations. This article aims to present and describe a prescriptive model to increase the quality of professional development of Iranian nurses within an organization-based framework. Materials and Methods: This article is an outcome of the results of a study based on grounded theory describing how Iranian nurses develop. The present study adopted purposive sampling and the initial participants were experienced clinical nurses. Then, the study continued by theoretical sampling. The present study involved 21 participants. Data were mainly collected through interviews. Analysis began with open coding and continued with axial coding and selective coding. Trustworthiness was ensured by applying Lincoln and Guba criteria such as credibility, dependability, and conformability. Based on the data gathered in the study and a thorough review of related literature, a prescriptive model has been designed by use of the methodology of Walker and Avant (2005). Results: In this model, the first main component is a three-part structure: Reformation to establish a value-assigning structure, a position for human resource management, and a job redesigning. The second component is certain of opportunities for organization-oriented development. These strategies are as follows: Raising the sensitivity of the organization toward development, goal setting and planning the development of human resources, and improving management practices. Conclusions: Through this model, clinical nurses' professional development can transform the profession from an individual, randomized activity into more planned and systematized services. This model can lead to a better quality of care.